Fluidized bed technology for biooil production: Review - Rangasamy, Mythili; Venkatachalam, P; Subramanian, P (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Fast pyrolysis is an emerging technique by which a liquid product, biooil is formed. The fast pyrolysis can be done using various reactors such as fluidized bed reactors, transported and circulating fluidized bed reactors, ablative and vacuum reactors, tubular reactors, microwave pyrolytic reactors,auger system and rotating cone reactors. Among them fluidized bed system is a well understood technology and available for the commercialization of fast pyrolysis. In this review, the process parameters in fluidized bed system that enhance the biooil production were reviewed. Utilization of various feedstocks for biooil production and the characteristics of biooil that mainly affect the utilization were presented. Â 